Phytochemical Analysis of Polar, Semipolar and Non-polar Fractions of Ethanol Extract of Jamblang Leaves (Syzygium cumini (L.)) and Antioxidant Test Using The DPPH (1,1-diphenyl-2-picrydhydrazyl) Method - Meiliza Ekayanti; Luqiaturrohmah, Putri; Hasan, Putri Zhafirah Maulida (Pharmaceutical Journal of Indonesia, 2025)
Abstract: Free radicals are atoms or groups of atoms with one or more unpaired electrons that are highly reactive and can cause damage to cells by binding to essential compounds such as lipids, proteins and DNA. Antioxidants are compounds that play a crucial role in protecting cells from oxidative stress caused by free radicals. Antioxidants inhibit or neutralize reactive oxygen species and mitigate oxidative damage to biomolecules, thereby reducing the risk of degenerative pathology and supporting homeostasis. This study aims to analyze the phytochemical compounds and determine the antioxidant activity of the polar, semi-polar, and non-polar fractions of the ethanol extract of Jamblang leaves (Syzygium cumini (L.)). The extraction method used was maceration with 96% ethanol, which was evaporated to obtain a concentrated ethanol extract with a yield of 10.321%. Fractionation was performed by dissolving the extract in polar water and then partitioning with non-polar n-hexane. The water layer was further fractionated using semipolar ethyl acetate. The yields from the fractionation were 12.48% for the water fraction, 18.41% for the ethyl acetate fraction and 1.76% for the n-hexane fraction. The compounds contained in the jamblang leaf fractions include alkaloids, flavonoids, tannins, steroids and saponins. Identification through thin-layer chromatography (TLC) with quercetin as a reference showed the same Rf value of 0.92, indicating the presence of flavonoid compounds. Under UV light at 366 nm, a red-purple fluorescence was observed, indicating the presence of terpenoid steroids. The antioxidant activity was tested using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method with ascorbic acid and quercetin as positive controls. The IC50 values ​​obtained were 35.406±46.410 for the water fraction, 237.623±205.1 for the ethyl acetate fraction and 39.961 ppm for the n-hexane fraction. The conclusion of this study is that the jamblang leaf fractions contain alkaloids, flavonoids, tannins, steroids and saponins. Exhibit very strong antioxidant activity in the water fraction, moderate antioxidant activity in the ethyl acetate fraction and very strong antioxidant activity in the n-hexane fraction.